Symposium 9: Academic Use of Digital Resources: Disciplinary Differences and the Issue of Progression - Jones, Chris; Zenios, Maria; Griffiths, Jill (Proceedings of the International Conference on Networked Learning, 2004)
This paper examines the use of digital resources by academics in UK Higher education. The explosive growth of the Internet and in particular the Web has led to a growth in speculation about networked and e-learning (Steeples and Jones 2003, Brown and Duguid 2000). Increasingly researchers have become aware of the ways the university resists such changes and provides a ‘resourceful constraint’ to the changes surrounding the introduction of networked learning (Brown and Duguid 2000, Cornford 2002). The take-up and use of digital resources by academic staff will be a critical factor in the success of attempts to integrate networked technologies into university teaching. There has been little research work to date that investigates the ways in which academic practice varies in relation to digital resources although there is a significant tradition of research concerned more broadly with disciplinary differences amongst academics. Two key issues are identified, different discipline and subject areas show significant divergence in the types and uses of digital resources and progression seems to affect the use of resources within the different disciplines. The research supports the view that disciplinary and subject differences reported in other contexts have a significant influence in relation to the use of digital resources.